MENUMBUHKAN KARAKTER DI SEKOLAH DASAR MELALUI PEMBELAJARAN KEWARGANEGARAAN, BAHASA INDONESIA DAN TEKNOLOGI - Intansari, Ilfi; Gustianti, Arita; Annisa Risqi Sulistya Kusuma Wardhani; Lulu Fatihatul Uyun; Nabila Rahma Qadrsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted to increase students' awareness of character education, literacy, and digitalization in elementary school learning. The research took place at SDIT La Tahzaan Citra Raya with 20 students as participants. Data were obtained from Pre-Test and Post-Test assessments conducted before and after the counseling session. Based on the collected data, the results showed an improvement in students' perceptions of character education, literacy, and technology. This study is expected to serve as an initial step to encourage further actions in enhancing character education, literacy, and technology-based learning for elementary school students.